Bots and Misinformation Spread on Social Media: Implications for COVID-19 - Himelein-Wachowiak, McKenzie; Giorgi, Salvatore; Devoto, Amanda; Rahman, Muhammad; Ungar, Lyle; Schwartz, H Andrew; Epstein, David H; Leggio, Lorenzo; Curtis, Brenda (JMIR Publications, 2021)
As of March 2021, the SARS-CoV-2 virus has been responsible for over 115 million cases of COVID-19 worldwide, resulting in over 2.5 million deaths. As the virus spread exponentially, so did its media coverage, resulting in a proliferation of conflicting information on social media platforms-a so-called "infodemic." In this viewpoint, we survey past literature investigating the role of automated accounts, or "bots," in spreading such misinformation, drawing connections to the COVID-19 pandemic. We also review strategies used by bots to spread (mis)information and examine the potential origins of bots. We conclude by conducting and presenting a secondary analysis of data sets of known bots in which we find that up to 66% of bots are discussing COVID-19. The proliferation of COVID-19 (mis)information by bots, coupled with human susceptibility to believing and sharing misinformation, may well impact the course of the pandemic.